Meaning in life and resilience to stressors. Issue 6 (1st November 2020) - Ostafin, Brian D.; Proulx, Travis
ABSTRACT: Background: and Objectives: This research examined whether life meaning promotes resilience to stressor-related psychological distress and repetitive negative thinking. Design and Methods: Three studies (total N  = 273) used cross-sectional (Study 1) and prospective (Studies 2 and 3) designs to assess the relation between life meaning and response to various stressors. Results: Results showed that in Study 1, greater life meaning was inversely related with repetitive negative thinking and psychological distress. Further, a mediation analysis showed an indirect effect for the life meaning-repetitive negative thinking relation through psychological distress. In Study 2, baseline life meaning predicted less repetitive negative thinking about a subsequent city-wide flood. In Study 3, baseline life meaning was inversely related to distress and repetitive negative thinking after writing about an aversive memory. A mediation analysis showed an indirect effect for the life meaning-repetitive negative thinking relation through distress. Conclusions: In all studies, life meaning predicted outcomes when controlling for other positive well-being variables. Overall, the findings suggest that individuals with greater trait life meaning experience less stressor-related distress and repetitive negative thinking and that the life meaning-repetitive negative thinking relation may be mediated by distress.